STUDY OF POISON GAS OCCURRENCE AND WATER QUALITY WITHIN BAUXITE-CARRYING BARGE AT KIJANG ISLAND - AHMAD FUAD AZMI TANJUNG (Indonesian Mining Journal, 2006)
An accident occurred in bauxite-carrying barge at Kijang Island that caused the death of 3 workers urged Mining Business Unit for Bauxite of PT Aneka Tambang to ask RDCMCT to conduct a series research on the barge. Observation on the site sampled gas and water. Results presented that NO2, SO2 and CO contents were still the threshold value as stated in a circular of Minister of Manpower no. SE.01/MEN/1997. Seawater analyses showed that all elements were still below the allowed figures except for nitrogen-ammonia (N-NH3) that exceeded the threshold value (0.213-0.47 mg/l). Based on observation on the site and laboratory analyses, oxygen deficiency within compartment was the caused of the worker death.